PENERAPAN STRATEGI E-MARKETING COMMUNICATION DAN EKUITAS MEREK SIARANKU.COM TERHADAP LOYALITAS VIEWERS - Putri Dewi Ikhsana; Guntur Freddy Prisanto; Rosita Anggraini (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2019)
The development of communication technology has brought changes to the patterns of human interaction behavior which continue competing to innovate in developing and utilizing increasingly sophisticated communication technologies. In this study, researchers were using theories and concepts that support the basis of being integrated, such as Integrated Marketing Communication, Brands, Brand Equity, and Consumer Loyalty. Researchers were using a supportive method to be used as a methodology such as positivistic paradigm, quantitative approach, survey strategy using questionnaires, sampling techniques using the formula taro yamane, and data processing techniques using probability sampling - simple random sampling. The results showed that e-marketing communication and brand equity have a strong influence on the loyalty of siaranku.com viewers and have a validity level that meets the requirements.